Relacje matki i córki w "Jędzy Elizy Orzeszkowej" = The mother-daughter relationship in "The Shrew" ["Jędza"] by Eliza Orzeszkowa - Banot, Aleksandra E. (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
A few historians of literature have written about "The Shrew" ["Jędza"] (1891) by Eliza Orzeszkowa. Apart from a few reviews, it is difficult to find studies or even references to the novel. Yet, this narrative does not only illustrate the end of the nineteenth century society - it is also a thorough study of the relation between the mother and a daughter.
Keywords: Orzeszkowa, Eliza (1841-1910) - twórczość; "Jędza"; literatura - 19 w.; mit o Antygonie; psychologia relacji matka-córka; "The Shrew"; 19th century literature; the myth of Antigone; psychology of mother-daughter relationship